Transforming Transportation Law: Consumer Protection and Law Enforcement at PT. Pos Indonesia - Arikha Saputra; Budi Santoso; Budi Ispiyarso; Adi Suliantoro; Fitka Andraini (Universitas Negeri Semarang, 2026)
This research examines changes in the legal landscape in the freight transportation sector at PT. Pos Indonesia, particularly in terms of protecting consumers and enforcing laws related to damaged, lost, or delayed shipments. The research background is based on the rapid development of digital technology and e-commerce, which are driving changes in the freight transportation industry. This has prompted PT. Pos Indonesia to adapt its service systems and existing regulations to protect consumer rights. The research method used is a normative juridical approach, referring to laws and legal concepts. This approach aims to understand the applicable regulations and legal principles underlying consumer protection in the freight transportation sector. The results of the study indicate that although PT. Pos Indonesia has implemented several digital innovations to improve service efficiency, significant challenges remain in law enforcement, particularly in the consumer claims process. The complicated claims process and lack of transparency in procedures are major obstacles to providing adequate protection to consumers. Therefore, regulatory improvements are needed to better align with technological developments, as well as the development of a faster and more transparent claims system. This research also provides policy recommendations to strengthen shipping insurance and improve consumer education about their rights to optimize legal protection. These reforms are expected to improve consumer protection in the freight sector and strengthen customer trust.